Design of experimental vehicle specified for competition Shell Eco-marathon 2017 according to principles of car body digitisation based on views in 2D using the intuitive tool Imagine&Shape CATIA V5. (January 2018) - Fabian, Michal; Puškár, Michal; Boslai, Róbert; Kopas, Melichar; Kender, Štefan; Huňady, Róbert
Highlights: Shell Eco-marathon and Building of Experimental Vehicle. Intuitive Tool for Creation of Surface Model in CATIA V5. Design with Imagine&Shape. Rapid Prototyping. Aerodynamics analysis. Abstract: Materialisation of every new great idea requires performing of many activities, including application of the latest CA-technologies. Nowadays the design process concerning the exterior and interior parts of a motorcar is unthinkable without utilisation of the CAD support. Although the primary impulses, new ideas or inspirations are arising in the minds of customers, businessmen and managers, the realisation process itself is always a serious task for the engineers in order to create a final shape, taking into consideration the customer's requirements. The experimental vehicles represent a special category of the motorcars. Design of the experimental vehicles demands a specific approach with regard to the above-standard requirements concerning vehicle aerodynamics, reduced rolling resistances and low-level fuel consumption of the vehicle engine.